Cometabolic degradation of chlorinated alkenes by alkene monooxygenase in a propylene-grown Xanthobacter strain. - Ensign, S A (1992)
Propylene-grown Xanthobacter cells (strain Py2) degraded several chlorinated alkenes of environmental concern, including trichloroethylene, 1-chloroethylene (vinyl chloride), cis- and trans-1,2-dichloroethylene, 1,3-dichloropropylene, and 2,3-dichloropropylene. 1,1-Dichloroethylene was not degraded efficiently, while tetrachloroethylene was not degraded. The role of alkene monooxygenase in catalyzing chlorinated alkene degradations was established by demonstrating that glucose-grown cells which lack alkene monooxygenase and propylene-grown cells in which alkene monooxygenase was selectively inactivated by propyne were unable to degrade the compounds. C2 and C3 chlorinated alkanes were not oxidized by alkene monooxygenase, but a number of these compounds were inhibitors of propylene and ethylene oxidation, suggesting that they compete for binding to the enzyme. A number of metabolites enhanced the rate of degradation of chlorinated alkenes, including propylene oxide, propionaldehyde, and glucose. Propylene stimulated chlorinated alkene oxidation slightly when present at a low concentration but became inhibitory at higher concentrations. Toxic effects associated with chlorinated alkene oxidations were determined by measuring the propylene oxidation and propylene oxide-dependent O2 uptake rates of cells previously incubated with chlorinated alkenes. Compounds which were substrates for alkene monooxygenase exhibited various levels of toxicity, with 1,1-dichloroethylene and trichloroethylene being the most potent inactivators of propylene oxidation and 1,3- and 2,3-dichloropropylene being the most potent inactivators of propylene oxide-dependent O2 uptake. No toxic effects were seen when cells were incubated with chlorinated alkenes anaerobically, indicating that the product(s) of chlorinated alkene oxidation mediates toxicity.